The Theory of the Earth Energy: Academia and the Vernacular in Search of the Supernatural. (13th August 2015) - Kivari, Kristel
Abstract : Using the concept of "implicit religion, " this article attempts to show how the broad field of vernacular ideas and practices, related to the "forces beyond, " provide an explanation for living in general. The idea that reality is shaped by an imperceptible "force" or "radiation, " which has an impact on human health and cognition, is the background for curiosity about dowsing practices. The discussions of early miners in Germany show the accommodation of vernacular practice within the framework of natural science and technology during the early modern period. A similar approach was also present at the end of the 1980s when the Baltic Dowsers' Association formulated its activities, as seen in the collections of articles generated by their periodical conferences. The article concludes with an analysis of the formulation of vernacular truth about Earth energies alongside the material sciences, and presents the usage of such place legends and vernacular practices in the fringes of Academia.